Potential for nontuberculous mycobacteria proliferation in natural and engineered water systems due to climate change: A literature review. (August 2021) - Blanc, S.M.; Robinson, D.; Fahrenfeld, N.L.
Graphical abstract: Highlights: Climate change (e.g., temperature, eutrophication) may increase habitat suitability for NTM. Innovative water treatment and distribution practices may reduce NTM proliferation. Embracing a One Water approach to manage water scarcity may mitigate NTM exposure. Collaborative study of NTM response to evapotranspiration, permafrost thaw needed. Abstract: Nontuberculous mycobacterial (NTM) infections are costly, difficult to treat, and increasing in prevalence. Given this, there is a desire to understand the potential relationships between NTM in water sources and climate change stressors. To address this need, a critical literature review was performed. Connections were made between NTM fate and transport, climate change, engineering decisions, and societal changes, and uncertainties highlighted. Environmental conditions discussed with respect to NTM risk included changing temperature, humidity, salinity, rainfall, and extreme weather events. NTM risk was then considered under climate/societal scenarios described by Intergovernmental Panel on Climate Change (IPCC) scientists. Findings indicate that the resilience of NTM under a variety of environmental conditions (e.g., warm temperatures, eutrophication) may increase their net prevalence in water environments under climate change, increasing exposure. Water management decisions may also influence exposure to NTM as water scarcity is expected to result in increased reliance on reclaimed water. Water managers may control risk of exposure through innovative water treatment processes and equitable water management decisions, turning towards an integrated One Water approach to reduce and/or mitigate the impacts of de facto reuse. Future research recommendations are provided including studies into potential changes to NTM fate and transport in uniquely impacted climates (e.g., boreal regions), and investigations into the relative risk of managed aquifer recharge as compared to no action.